RETHINKING THE DETERMINANTS OF LABOUR PRODUCTIVITY IN NIGERIA: A QUEST FOR LABOUR EFFICIENCY AND LOW COST PER UNIT OF OUTPUT (Journal of Contemporary Issues in Accounting, 2022)
This paper examined the determinants of labour productivity in Nigeria over the period 1990 to 2020 by looking at the factors that influence labour output and reduces the cost of production per unit. Determinants of labour productivity were represented by the human capital development index, capital intensity, wage rate, per capita income, globalization index, governance and usage of information and communication technology. The auto-regressive distributed lag (ARDL) model was used for the data estimation and analysis. From the results, it was found that the explanatory variables, human capital development index, capital intensity, wages, globalization index, governance and application of ICT exerted negative effects on labour productivity in the short run, while, per capita income had a positive effect. In the long run, human capital development, capital intensity, per capita income and information and communication technology usage appeared to have the most significant effect on labour productivity in Nigeria. The study recommends that Nigeria should take advantage of globalization to attract foreign resources and knowledge to enhance the efficiency of labour in the country. Consequently, there is a need for trade liberalization that will permit new technology and innovation transfer needed for the upgrade of workers' skills. It further recommends improvement in public administration, institutional reforms and application of appropriate policies and regulations towards promoting and enhancing workers’ wages and encourages them to acquire more knowledge through training, seminars and conferences.
Keywords: Labour; efficiency; productivity; human capital; wages; ICT; governance